AGE-RAGE Axis in the Pathophysiology of Chronic Lower Limb Ischemia and a Novel Strategy for Its Treatment - Prasad, Kailash; Bhanumathy, Kalpana K. (International Journal of Angiology, 2020)
This review focuses on the role of advanced glycation end products (AGEs) and its cell receptor (RAGE) and soluble receptor (sRAGE) in the pathogenesis of chronic lower limb ischemia (CLLI) and its treatment. CLLI is associated with atherosclerosis in lower limb arteries. AGE-RAGE axis which comprises of AGE, RAGE, and sRAGE has been implicated in atherosclerosis and restenosis. It may be involved in atherosclerosis of lower limb resulting in CLLI. Serum and tissue levels of AGE, and expression of RAGE are elevated, and the serum levels of sRAGE are decreased in CLLI. It is known that AGE, and AGE-RAGE interaction increase the generation of various atherogenic factors including reactive oxygen species, nuclear factor-kappa B, cell adhesion molecules, cytokines, monocyte chemoattractant protein-1, granulocyte macrophage-colony stimulating factor, and growth factors. sRAGE acts as antiatherogenic factor because it reduces the generation of AGE-RAGE-induced atherogenic factors. Treatment of CLLI should be targeted at lowering AGE levels through reduction of dietary intake of AGE, prevention of AGE formation and degradation of AGE, suppression of RAGE expression, blockade of AGE-RAGE binding, elevation of sRAGE by upregulating sRAGE expression, and exogenous administration of sRAGE, and use of antioxidants. In conclusion, AGE-RAGE stress defined as a shift in the balance between stressors (AGE, RAGE) and antistressor (sRAGE) in favor of stressors, initiates the development of atherosclerosis resulting in CLLI. Treatment modalities would include reduction of AGE levels and RAGE expression, RAGE blocker, elevation of sRAGE, and antioxidants for prevention, regression, and slowing of progression of CLLI.
Keywords: advanced glycation end products (AGE); cell receptor for AGE; soluble receptor for AGE; AGE-RAGE stress; chronic lower limb ischemia; atherosclerosis; treatment of chronic lower limb ischemia